Comparative Assessment on Laryngeal Function after Radiotherapy and Laser Surgery against Early Glottic Cancer. (23rd August 2013) - Kono, Takeyuki; Saito, Koichiro; Yabe, Haruna; Uno, Kosuke; Ogawa, Kaoru
Abstract : Objectives: Comparatively assess the laryngeal function and quality of life (QOL) of the patients after laser surgery and radiotherapy against early glottic cancer. Methods: Sixty‐seven patients with T1 glottic cancer treated in our institution with radiotherapy (RT, n=30) or CO2 laser surgery (LS, n=37) were incorporated in this retrospective cohort study. LSs were performed following the type II subligamental cordectomy concept. Patients in LS group were categorized into subgroups for further analyses. Twenty‐seven patients had vaporization of the lesion with defocused mode, and a residual 10 patients had cancer excision with focused mode using relatively lower power (LS‐EX group). GRBAS subjective voice assessment scale, maximum phonation time, and acoustic parameters were measured as vocal parameters. Voice‐Related Quality of Life Measure and Voice Handicap Index were used to evaluate post‐therapeutic QOL. Laryngeal videostroboscopic images were further examined to assess post‐therapeutic laryngeal pliability. The mean follow‐up period was 46 months. Results: Compared with their pre‐therapeutic scores, worse GRBAS scores were observed at the end of the treatments in 20% and 60% of RT group and LS group respectively. Although these scores recovered 1 year after treatment, abnormal stroboscopic findings remained in 40% and 95% of RT group and LS group respectively. Interestingly, further subgroup analysis proved no significant difference of post‐therapeutic vocal parameters and QOL between RT group and LS‐EX group. Conclusions: Early glottic cancer could be treated with equivalent post‐therapeutic laryngeal function and QOL with either radiotherapy or focused low power CO2 laser surgery.